The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1143/jjap.39.4816
|View full text |Cite
|
Sign up to set email alerts
|

Formation of pn Homojunction in Cu(InGa)Se2 Thin Film Solar Cells by Zn Doping

Abstract: In this study, a pn homojunction was intentionally fabricated in the Cu(InGa)Se2 (CIGS) layer by Zn doping. For Zn doping of the CIGS layer, Zn was evaporated after CIGS formation, and a potential improvement in cell performance was confirmed by this technique. Furthermore, Zn diffusion into the CIGS film was investigated by secondary ion mass spectroscopy (SIMS). A conductivity-type conversion from p-type to n-type was studied by the measurement of the cross-sectional electron beam-induced current (junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 6 publications
2
23
0
Order By: Relevance
“…In addition, Zn-doped CIGS layers can be formed by simple dry processes such as chemical vapor deposition, thermal evaporation, and thermal diffusion. However, few experimental results have been reported for the fabrication of pn junction using Zn-doped CuInSe 2 (CIS) bulk crystals [4][5][6][7][8] or CIGS films [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zn-doped CIGS layers can be formed by simple dry processes such as chemical vapor deposition, thermal evaporation, and thermal diffusion. However, few experimental results have been reported for the fabrication of pn junction using Zn-doped CuInSe 2 (CIS) bulk crystals [4][5][6][7][8] or CIGS films [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the CIGS film Zn doped at 1st stages exhibited increase in carrier concentration ( p = 10 16 ≈ 10 17 cm −3 ) which is higher than that of the corresponding undoped CIGS film by one order of magnitude. This result is in contrast to the n‐type conductivity of the CIGS films when Zn is doped at 2nd and 3rd stages . The solar cell using such p‐CIGS:Zn film exhibited V oc = 0.66V, I sc = 32 mA/cm 2 , FF = 69%, and η = 14.5%, which are higher than the corresponding intentionally undoped CIGS solar cells.…”
Section: Introductionmentioning
confidence: 73%
“…Other effects related to n-type doping transitions and intermediate-band creation due to Zn and Sn doping, respectively, occur at much higher concentrations [107]- [109] and are unlikely to be a contributing factor to reduced device performance. Little is known of the effect of other impurities.…”
Section: B Impurity Issuesmentioning
confidence: 99%